EVALUASI IMPLEMENTASI PROGRAM ADIWIYATA DI SEKOLAH DASAR MULYA ASRI CIKUPA KABUPATEN TANGERANG MELALUI MODEL CIPP - Muhamad Ariq Fakhri Rabani; Ina Magdalena; Dayu Retno Puspita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study explores the implementation of the Adiwiyata Program at Mulya Asri Elementary School in Cikupa, Tangerang Regency, using the CIPP evaluation model (Context, Input, Process, Product). The research focuses on how school policies, stakeholder involvement, and the availability of facilities contribute to fostering an environmentally conscious culture. Employing a descriptive qualitative approach, data were collected through field observations, in-depth interviews, and document analysis, involving the principal, teachers, students, and school janitors. The findings reveal that, contextually, the school upholds a clear vision and mission aligned with environmental awareness. In terms of input, supporting facilities are available though not yet evenly distributed, while the active engagement of teachers, students, and staff is evident. The process dimension shows that environmental activities are conducted regularly, systematically, and integrated into learning. As for product, the program positively shapes students’ eco-friendly behavior and enhances the school’s institutional image. Overall, the Adiwiyata Program runs effectively, though continuous innovation and equitable facilities are needed for stronger sustainability.